2021
DOI: 10.1111/iju.14492
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines for Female Lower Urinary Tract Symptoms (second edition)

Abstract: The present article is an abridged English translation of the Japanese Clinical Guidelines for Female Lower Urinary Tract Symptoms (second edition), published in September 2019. These guidelines consist of a total of 212 pages and are unique worldwide in that they cover female lower urinary tract symptoms other than urinary incontinence. They contain two algorithms for "primary treatment" and "specialized treatment," respectively. These guidelines, consisting of six chapters, address a total of 26 clinical que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 231 publications
(290 reference statements)
1
39
0
Order By: Relevance
“…Tension-free vaginal tape (TVT) surgery for stress urinary incontinence is strongly recommended by guidelines, but rarely results in severe complications. 1 In past reports, TVT has been associated with more bladder perforation than transobturator tape, 2 which is attributed to the route of tape insertion. Watanabe et al reported a rare case of tape infection 19 years after insertion of a TVT.…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tension-free vaginal tape (TVT) surgery for stress urinary incontinence is strongly recommended by guidelines, but rarely results in severe complications. 1 In past reports, TVT has been associated with more bladder perforation than transobturator tape, 2 which is attributed to the route of tape insertion. Watanabe et al reported a rare case of tape infection 19 years after insertion of a TVT.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The treatment of SUI includes physical therapy, medication, and surgery 1 . Insertion of TVT, one of the minimally invasive techniques used for women with SUI, is widely performed because of its efficacy, but its complications cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, storage symptoms significantly affected quality of life. 13 A previous report suggested that the incidence of OAB symptoms in women increases with an increase in their age. 14 Thus, it was clinically important to elucidate the factors responsible for the development of LUTS, especially the storage symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…Tension‐free vaginal tape (TVT) surgery for stress urinary incontinence is strongly recommended by guidelines, but rarely results in severe complications. 1 In past reports, TVT has been associated with more bladder perforation than trans‐obturator tape, 2 which is attributed to the route of tape insertion. Watanabe et al.…”
mentioning
confidence: 99%